Evaluation of the Rapid Polymyxin NP Test for Polymyxin B Resistance Detection Using Enterobacter cloacae and Enterobacter aerogenes Isolates - Simar, Shelby; Sibley, Diane; Ashcraft, Deborah; Pankey, George (Journal of clinical microbiology, 2017)
Polymyxin resistance is an increasing problem worldwide. Currently, determining susceptibility to polymyxins is problematic and lengthy. Polymyxins diffuse poorly into agar, potentially giving inaccurate disk diffusion and Etest results. A rapid screening test (2 h) for the detection of polymyxin resistance in Enterobacteriaceae , developed by P. Nordmann and L. Poirel (rapid polymyxin NP test) in 2016, detects glucose metabolization in the presence of polymyxin E (PE) and PB via pH-induced color change. The sensitivity and specificity were 99.3 and 95.4%, respectively, with results obtained in ≤2 h. Our goal was to evaluate this test using PB against larger numbers of Enterobacter . A total of 143 nonduplicate Enterobacter isolates (102 E. cloacae complex, 41 E. aerogenes ) were tested, including 136 collected from Ochsner Health System patients from March to May 2016 and 7 previously determined PB-resistant E. cloacae isolates from JMI Laboratories. MICs were determined via broth microdilution. For the rapid polymyxin NP test, a color change from orange to yellow is positive; a weak/no color change is deemed negative after 4 h. Of 143 Enterobacter isolates, 25 were determined to be PB resistant by broth microdilution (MIC > 2 μg/ml), including all 7 JMI isolates. Of these 25, 7 were positive by the rapid polymyxin NP test (included 3/7 JMI isolates). All 118 isolates determined to be PB susceptible by broth microdilution were NP test negative. The sensitivity and specificity for the rapid polymyxin NP test were 25 and 100%, respectively, compared to broth microdilution. Although the rapid polymyxin NP test is a much faster method (2 to 4 h) for polymyxin resistance determination compared to broth microdilution (16 to 20 h), our study indicates that it may be subject to limitations when testing Enterobacter .